2017
DOI: 10.2147/ijn.s143264
|View full text |Cite
|
Sign up to set email alerts
|

Engineered outer membrane vesicle is potent to elicit HPV16E7-specific cellular immunity in a mouse model of TC-1 graft tumor

Abstract: Purpose Currently, therapeutic tumor vaccines under development generally lack significant effects in human clinical trials. Exploring a powerful antigen delivery system is a potential approach to improve vaccine efficacy. We sought to explore engineered bacterial outer membrane vesicles (OMVs) as a new vaccine carrier for efficiently delivering tumor antigens and provoking robust antitumor immune responses. Materials and methods First, the tumoral antigen human papillo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 36 publications
(33 reference statements)
3
41
0
Order By: Relevance
“…OMVs are released in greater abundance from Gram-negative than Gram-positive bacteria, are crucial for bacterial survival and form part of the stress response (McBroom and Kuehn, 2007; Macdonald and Kuehn, 2013; Jan, 2017). Research on bacterial OMVs has grown rapidly in recent years, including their use as bioengineered drug delivery vehicles (Gujrati et al, 2014; Bitto and Kaparakis-Liaskos, 2017) and in vaccine development (Gaillard et al, 2014; Choi et al, 2015; Alves et al, 2016; Raeven et al, 2016; Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…OMVs are released in greater abundance from Gram-negative than Gram-positive bacteria, are crucial for bacterial survival and form part of the stress response (McBroom and Kuehn, 2007; Macdonald and Kuehn, 2013; Jan, 2017). Research on bacterial OMVs has grown rapidly in recent years, including their use as bioengineered drug delivery vehicles (Gujrati et al, 2014; Bitto and Kaparakis-Liaskos, 2017) and in vaccine development (Gaillard et al, 2014; Choi et al, 2015; Alves et al, 2016; Raeven et al, 2016; Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…LPS in the outer surface of OMVs acts as a self-adjuvant that induces humoral and cellular immunity. Therefore, OMVs vaccines may be used without extra adjuvant to increase the immunogenicity and produce antiviral innate immune responses against various influenza virus infections via activation of macrophages [42,43,44]. Despite that the exact role of LPS in the context of OMVs vaccines requires further investigations, high amounts of LPS could be a drawback due to its known endotoxicity and ability to induce excessive secretions of pro-inflammatory cytokines [45].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, OMVs are 50–250 nm in diameters, making OMVs great carriers for efficient lymph node homing and intracellular delivery into APCs (Lin, Chattopadhyay, Lin, & Hu, ). Up to now, OMVs have been studied to develop bacterial vaccines (Lin et al, ) and more recently cancer therapeutic vaccines (Kim et al, ; Wang et al, ). For instance, OMVs were loaded with antitumor cytokines CXCL10 and interferon‐γ as therapeutic agents (Kim et al, ), which showed remarkable efficacy to induce long‐term antitumor immune responses that eradicated established tumors without notable adverse effects.…”
Section: What Makes Cancer Nanovaccines?mentioning
confidence: 99%
“…Further, engineered OMVs have been engineered to display Human Papillomavirus 16 (HPV16) E7 protein to induce E7‐specific cellular immunity. These OMVs showed significant therapeutic efficacy, thus demonstrating the potential of OMVs as cancer nanovaccines (Wang et al, ).…”
Section: What Makes Cancer Nanovaccines?mentioning
confidence: 99%